Strategi Pemberdayaan Kelompok Petani Garam di Kampung Greges Kota Surabaya - Amelia Jihan Fahnanda; Diana Hertati (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
The aim of this research is to find out and describe empowerment strategies for groups of salt farmers in Greges Village, Tambak Sarioso Village. Descriptive qualitative methods were used in this research with data collection techniques through observation, interviews and documentation. The results of this research show that the empowerment carried out for kelompok petani garam di Kampung Greges, Kelurahan Tambak Sarioso was carried out using 3 strategy variables, namely first, the aras mikro by providing guidance and crisis intervention which was carried out by holding regular meetings with the Lembaga Pemberdayaan Masyarakat Kelurahan (LPMK) Tambak Sarioso. The second strategy is the aras mezzo through training conducted by the Dinas Ketahanan Pangan dan Pertanian Kota Surabaya regarding the use of geomembranes. The third strategy is the macro level which is carried out with social planning, community organizing and conflict management. This effort was made to minimize the inequality in salt prices between farmers and increase the ability of salt farmers to be more empowered.